Orthorexia nervosa: an investigation in the context of personality, body image, and physical activity - Genç, Halil İbrahim and Hepsert, Sezgin and Öktem, Tuncay and Kiratli, Tuncay and Yildirim, Yavuz and İlgin, Özgecan (Frontiers in Psychology, 2025)
This study aimed to examine the relationship between orthorexia nervosa and body image, physical activity level, and the Big Five personality traits among non-clinical adult individuals. Based on the relational survey model, the research sample consisted of 350 undergraduate students (205 females, 145 males) enrolled in various departments at a public university. A convenience sampling method was used, and participants’ ages ranged from 18 to 30 years (M = 20.64, SD = 2.07). Data were collected using a personal information form, the ORTO-15 Scale, the Big Five Personality Test (short version), the Body Appreciation Scale, and the International Physical Activity Questionnaire. Pearson correlation and regression analyses were conducted. The findings revealed that conscientiousness, openness to experience, and body image were significantly associated with orthorexic tendencies. As levels of conscientiousness and openness to experience increased, behaviors related to orthorexia nervosa also tended to increase. Similarly, individuals with higher body image satisfaction exhibited more pronounced orthorexic tendencies. These results suggest that individual differences may play a determining role not only in healthy lifestyle choices but also in the potential development of these choices into pathological behaviors.